Biokinetic data and models for occupational intake of lanthanoids. (November 2014) - Leggett, Rich; Ansoborlo, Eric; Bailey, Michael; Gregoratto, Demetrio; Paquet, Francois; Taylor, David
Abstract Purpose: This paper reviews data related to the behavior of the lanthanoid elements (lanthanum through lutetium, atomic numbers 57–71) in the human body and proposes biokinetic models for internally deposited radio-lanthanoids in workers. Materials and methods: Published data on the following topics are reviewed and analyzed: Physico-chemical properties of the lanthanoids as indicators of the potential behavior of these elements in body fluids; the concentrations of the stable lanthanoids in the environment and human body; and results of biokinetic studies of radio-lanthanoids in human subjects and laboratory animals. Respiratory and systemic biokinetic models and gastrointestinal absorption fractions are developed or selected in an effort to represent the typical behavior of lanthanoids in adult humans. Results and conclusions: Generic (element-independent) absorption rates from the respiratory and alimentary tracts to blood and systemic biokinetic models are proposed. The systemic models are largely generic but include some element-specific parameter values to reflect regular changes with ionic radius in certain aspects of the behavior of the lanthanoids, particularly fractional deposition in liver and bone and early removal in urine.